Biogas adoption in Nepal: empirical evidence from a nationwide survey - Hari Katuwal (Heliyon, 2022)
Using nationally representative survey data, we identify and examine the determinants of biogas technology adoption in Nepal. Because of its dependence on biomass energy, the Government of Nepal has been promoting alternative sources of energy, particularly for rural households. Biogas has been identified and promoted as a viable alternative renewable energy source alongside many others. In addition to providing low-cost sustainable energy, biogas offers a wide range of additional benefits. Because of the many benefits of adopting biogas, the Government of Nepal has made expanding biogas technology a priority. Despite the policy priority and several benefits, the drivers and barriers to household-level biogas technology adoption have not been investigated at the national level. We use newly collected survey data to investigate the determinants and barriers to biogas adoption. We use probit models to quantify the marginal effect of these determinants on biogas adoption. Our analysis shows that income, land holdings and the number of livestock are key socioeconomic determinants of biogas adoption in Nepal. Our result suggests that households in the country's hilly region are less likely to adopt biogas indicating the difficulty of installing and operating biogas in mountain and hilly regions. The findings also indicate that lack of access to a bank and the number of biogas service providers are among the main obstacles to biogas adoption in Nepal. Our findings provide information that can make valuable contributions to the energy policy of developing countries for the sustainable development of alternative energies.